2001
DOI: 10.1177/01466210122031975
|View full text |Cite
|
Sign up to set email alerts
|

Robustness of Item Parameter Estimation Programs to Assumptions of Unidimensionality and Normality

Abstract: The effects of test dimensionality (one-or three-dimensional), distribution shape (normal, positively skewed, or platykurtic), and estimation program (BILOG, MULTILOG, or XCALIBRE) on the accuracy of item and person parameter estimates were assessed. The criterion was the root mean squared error of the difference between estimated and true parameter values. There was an interaction between program and dimensionality, indicating that the robustness of the unidimensionality assumption was a function of the estim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
81
0
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(92 citation statements)
references
References 53 publications
(82 reference statements)
6
81
0
2
Order By: Relevance
“…However, unidimensional IRT models are robust to moderate degrees of multidimensionality as defined by factor analyses, particularly where the dimensions are highly correlated and/or where the test/index length is more than 20 items and/or the sample size is more than 250 (Kirisci et al, 2001). Local independence is also an important assumption, i.e.…”
Section: Reliabilitymentioning
confidence: 99%
“…However, unidimensional IRT models are robust to moderate degrees of multidimensionality as defined by factor analyses, particularly where the dimensions are highly correlated and/or where the test/index length is more than 20 items and/or the sample size is more than 250 (Kirisci et al, 2001). Local independence is also an important assumption, i.e.…”
Section: Reliabilitymentioning
confidence: 99%
“…In IRT, where the application of unidimensional measurement models dominates, a number of studies have explored the robustness of item parameter estimates to violations of unidimensionality (e.g., Drasgow & Parsons, 1983;Folk & Green, 1989;Kirisci, Hsu, & Yu, 2001). This research has generally shown that if a strong general factor exists in the data, then the estimated IRT item parameters are relatively unbiased when fit to a unidimensional measurement model.…”
mentioning
confidence: 99%
“…Contrary to the beliefs held by many substantive researchers, simulation research indicates that results from IRT models can be nontrivially biased when the true population distribution is nonnormal (Abdel-fattah, 1994;Boulet, 1996;de Ayala & SavaBolesta, 1999;DeMars, 2003;Kirisci, Hsu, & Yu, 2001;Seong, 1990 ;Stone, 1992; van den Oord, 2005;Zwinderman & van den Wollenberg, 1990). Specifically, MML estimates of item parameters increase in bias as the distribution deviates further from normality (Boulet, 1996;Stone, 1992;Woods, 2006Woods, , 2007aWoods, , 2007bWoods, , 2008Woods & Lin, 2009;Woods & Thissen, 2006).…”
Section: Effects Of Nonnormalitymentioning
confidence: 97%